A new EV71 VP3 epitope in norovirus P particle vector displays neutralizing activity and protection in vivo in mice. Issue 48 (27th November 2015) - Jiang, Liping; Fan, Rongjun; Sun, Shiyang; Fan, Peihu; Su, Weiheng; Zhou, Yan; Gao, Feng; Xu, Fei; Kong, Wei; Jiang, Chunlai
Highlights: Amino acids 176–190 in EV71 VP3 form a new broadly neutralizing conformational epitope. The novel VP3 epitope may aid vaccine development for hand, foot and mouth disease. Chimeric norovirus P particle with amino acids 176–190 of EV71 VP3 may aid dual vaccine design against EV71 and norovirus. Abstract: Enterovirus 71 (EV71) and Coxsackievirus A16 (CVA16), as the main agents causing hand, foot and mouth disease (HFMD), have become a serious public health concern in the Asia-Pacific region. Recently, various neutralizing B cell epitopes of EV71 were identified as targets for promising vaccine candidates. Structural studies of Picornaviridae indicated that potent immunodominant epitopes typically lie in the hypervariable loop of capsid surfaces. However, cross-neutralizing antibodies and cross-protection between EV71 and CVA16 have not been observed. Therefore, we speculated that divergent sequences of the two viruses are key epitopes for inducing protective neutralizing responses. In this study, we selected 10 divergent epitope candidates based on alignment of the EV71 and CVA16 P1 amino acid sequences using the Multalin interface page, and these epitopes are conserved among all subgenotypes of EV71. Simultaneously, by utilizing the norovirus P particle as a novel vaccine delivery carrier, we identified the 71-6 epitope (amino acid 176–190 of VP3) as a conformational neutralizing epitope against EV71 in an in vitro micro-neutralization assay as well as an in vivo protection assay in mice. Altogether, these results indicated that the incorporation of the 71-6 epitope into the norovirus P domain can provide a promising candidate for an effective synthetic peptide-based vaccine against EV71.